The role of work engagement and psychological safety in how socially responsible human resources management affects employee voice behaviour - Silva, V. H.; Duarte, A. P. (International Journal of Organizational Analysis, 2025)
Purpose This study aims to explore the role of socially responsible human resource management (SRHRM) as a key driver of employee voice behaviour. The hypotheses included that these human resources management (HRM) practices strengthen employees’ motivation to voice their opinions by increasing their work engagement (WE), thereby encouraging them to share their ideas and concerns about their organization more actively. The hypotheses also proposed that this effect is especially pronounced when employees experience a heightened sense of psychological safety. Design/methodology/approach A survey-based correlational study was conducted with a sample of 289 participants to analyse the proposed relationships between the selected variables. Findings The results indicate that SRHRM and WE are significantly associated with both promotive and prohibitive voice behaviour among employees. In addition, the moderated mediation model revealed that employees who perceive their organization as adopting SRHRM practices display higher levels of WE, which in turn increases these individuals’ likelihood of engaging in both types of voice behaviour. This relationship is particularly strong for promotive voice when employees experience high levels of organizational psychological safety. Research limitations/implications The findings are limited by the cross-sectional research design, which restricts causal inference. Practical implications By adopting people-centred HRM practices, organizations can foster psychologically safe environments that enhance employees’ willingness to engage in behaviour beneficial to their organization, such as WE and voice behaviours. Originality/value The results highlight the critical role of SRHRM and offer evidence-based insights into how interventions can foster positive employee behaviours and attitudes, including WE and voice behaviour.